(untitled) (Philological Studies, 2019)
In Macedonia the first graduated pharmacists are mentioned during the Middle Ages. Most pharmacists were from Dubrovnik; the first pharmacists arrived from Portugal and Spain of end of the 15th century and were Sephardic Jews. Within the framework in the Ottoman Empire, organized pharmaceutical activity started in the 19th century. The beginning of the 19th century saw the first Macedonian pharmacists. In 1840, there were two pharmacies in Bitola and Thessaloniki, owned by foreign pharmacists. At the end from the 19th century pharmacies opened and were active as part of the parish education councils in Veles, Bitola, Skopje and Thessaloniki.